Zehntneriana serrata n. sp., a new species of pilumnid crab from southern Taiwan (Crustacea, Decapoda, Brachyura) - Ng, Peter K. L.; Lin, Chia-Wei (Zootaxa, 2015)
A new species of rhizopine crab, Zehntneriana serrata (Pilumnidae) is described from a coral reef in southern Taiwan. The new species differs from congeners by its smooth and glabrous carapace, prominently serrated anterolateral margins, elongated ambulatory legs with a serrated anterior margin of the merus, and the diagnostic morphology of the male first gonopod.